BUDOWA I FUNKCJONOWANIE GMINNEJ OCZYSZCZALNI ŚCIEKÓW W WĄWELNIE Z UWZGLEDNIENIEM JEJ WPŁYWU NA ŚRODOWISKO - Babiński, Zygmunt; Kluza, Paulina; Tychoniec, Alicja Ewa (Journal of Education, Health and Sport, 2015)
Babiński Zygmunt, Kluza Paulina, Tychoniec Alicja. Budowa i funkcjonowanie gminnej oczyszczalni ścieków w wąwelnie z uwzglednieniem jej wpływu na środowisko = Construction and functioning of the municipal wastewater treatment facility in wąwelno including its impact on the environment. Journal of Education, Health and Sport. 2015;5(12):308-316. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35459 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A308-316 http://pbn.nauka.gov.pl/works/682133 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 16.12.2015. BUDOWA I FUNKCJONOWANIE GMINNEJ OCZYSZCZALNI ŚCIEKÓW W WĄWELNIE Z UWZGLEDNIENIEM JEJ WPŁYWU NA ŚRODOWISKO CONSTRUCTION AND FUNCTIONING OF THE MUNICIPAL WASTEWATER TREATMENT FACILITY IN WĄWELNO INCLUDING ITS IMPACT ON THE ENVIRONMENT Zygmunt Babiński, Paulina Kluza, Alicja Tychoniec IG, WKFZIT, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Abstrakt Celem artykułu jest szczegółowa analiza budowy i funkcjonowania oczyszczalni ścieków w Wąwelnie przeprowadzona na podstawie stosowanej dokumentacji i literatury. Uwzględnione zostało w tym aspekcie oddziaływanie na środowisko wodne. W artykule przedstawiono analizę przykładowych stężeń wybranych wskaźników zawartych w oczyszczonych ściekach oraz poruszono problem unieszkodliwienia osadów ściekowych z uwzględnieniem możliwości przeznaczenia tego osadu na cele przemysłowe. Słowa kluczowe: oczyszczalnia ścieków, budowa oczyszczalni ścieków, ścieki, rodzaje ścieków, osad ściekowy, wpływ na środowisko, gospodarka ściekowa. Abstract The purpose of this article is a detailed analysis of construction and functioning of the municipal waste treatment facility in Wąwelno conducted on the basis of appropriate documentation and literature. Impact on aquatic environment and water quality was included in this analysis. The article presents example concentration of chosen indicators in treated sewage as well as addresses the issue of sludge disposal and the possibility of its reuse for industrial purposes. Key words: sewage treatment facility, sewage treatment facility construction, sewage, types of sewage, sewage sludge, environmental impact, wastewater management.